Optimal management of umbilical cord prolapse - Sayed Ahmed WA; Hamdy MA (Dove Medical Press, 2018)
Waleed Ali Sayed Ahmed, Mostafa Ahmed Hamdy Department of Obstetrics and Gynecology, Faculty of Medicine, Suez Canal University, Ismailia, Egypt Abstract: Umbilical cord prolapse (UCP) is an uncommon obstetric emergency that can have significant neonatal morbidity and/or mortality. It is diagnosed by seeing/palpating the prolapsed cord outside or within the vagina in addition to abnormal fetal heart rate patterns. Women at higher risk of UCP include multiparas with malpresentation. Other risk factors include polyhydramnios and multiple pregnancies. Iatrogenic UCP (up to 50% of cases) can occur in procedures such as amniotomy, fetal blood sampling, and insertion of a cervical ripening balloon. The perinatal outcome largely depends on the location where the prolapse occurred and the gestational age/birthweight of the fetus. When UCP is diagnosed, delivery should be expedited. Usually, cesarean section is the delivery mode of choice, but vaginal/instrumental delivery could be tried if deemed quicker, particularly in the second stage of labor. Diagnosis-to-delivery interval should ideally be less than 30 minutes; however, if it is expected to be lengthy, measures to relieve cord compression should be attempted. Manual elevation of the presenting part and Vago’s method (bladder filling) are the most commonly used maneuvers. Care should be given not to cause cord spasm with excessive manipulation. Simulation training has been shown to improve/maintain all aspects of management and documentation. Prompt diagnosis and interventions and the positive impact of neonatal management have significantly improved the neonatal outcome. Keywords: umbilical cord prolapse, neonatal outcome, obstetric emergency, simulation training